Countrywide stroke incidence, subtypes, management and outcome in a multiethnic Asian population: the Singapore Stroke Registry – methodology. Issue 5 (5th March 2015) - Venketasubramanian, Narayanaswamy; Chang, Hui Meng; Chan, Bernard Poon Lap; Young, Sherry H.; Kong, Keng He; Tang, Kok Foo; Ang, Yan Hoon; Ahmad, Aftab; Chow, Khuan Yew; Singapore Stroke Registry
<x xml:space="preserve">Abstract</x> Rationale Because of its rapidly‐growing and aging populations, the global burden of stroke will be felt most strongly in Asia. Data from Asia are scarce. Even rarer are data from multiethnic populations. Aim The Singapore Stroke Registry is a countrywide registry of risk factors, stroke subtypes, management and outcome of incident and recurrent stroke in multiethnic Singapore. Methods and design Using a cold‐pursuit design, potential subjects are identified from medical claims, hospital discharge summaries and death certificates. Standardized methods are used for case ascertainment and data recording by trained staff into standardized case report forms. All ages and both genders are included. Study outcome Stroke incidence, subtypes and mortality will be calculated. Trend data will be obtained. Inter‐ethnic differences will be explored. Discussion The Registry has many features of an 'ideal' incidence study. Previously unavailable countrywide data on an Asian population will be acquired. The unique data on inter‐ethnic differences will help fill knowledge gaps in stroke epidemiology.